ANALISIS FAKTOR PSIKOLOGIS TERHADAP NIAT BELI JASA HOTEL PADA PENGGUNA ONLINE TRAVEL AGENT USIA MUDA DI JABODETABEK (PERSPEKTIF THEORY OF PLANNED BEHAVIOR) - Clevia Santoso; Puspita, Anggun Pesona Intan (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
Indonesia's tourism sector has shown significant recovery post-pandemic. This is indicated by the increase in domestic travel and high tourist spending on accommodation. Siteminder survey shows that 55% of Indonesian tourists book accommodation through online travel agents (OTAs), making it crucial to understand the factors influencing online hotel purchase intentions. One relevant theory in this context is the Theory of Planned Behavior (TPB), which assesses consumer behavior based on attitudes, subjective norms, and perceived behavioral control. Although numerous studies have discussed factors in hotel selection, studies applying the TPB to the context of OTAs are still limited. This study aims to analyze these three factors on hotel purchase intentions through OTAs in Jabodetabek area. The study used a quantitative approach by distributing questionnaires to 384 online travel agent users aged 18-44, which were then analyzed using multiple linear regression analysis. The results showed that attitude toward hotels, attitude toward OTAs, and perceived behavioral control had a partial influence on purchase intentions, while subjective norms had no influence. Furthermore, all four variables had a simultaneous influence on purchase intentions. For further research, it is recommended to expand the scope of respondents, add other variables, and use combined methods in data collection